Peer tutoring method to improve the Physics learning outcomes of grade XII students of Senior High School 1 Bambanglipuro - Jumiyati, Jumiyati; Ferawati, Denny Indria (DRPM UNY, 2025)
This study addresses the urgent need to enhance the effectiveness of physics education, particularly in light of the challenges faced by students in mastering complex scientific concepts. This study employed Classroom Action Research (CAR) to examine the effectiveness of the peer tutoring method in enhancing physics learning outcomes at Senior High School 1 Bambanglipuro. Conducted over two cycles, each consisting of two face-to-face meetings, the research followed the iterative process of planning, action, observation, and reflection. The research subjects were 32 students from class XII MIPA 3 during the 2020-2021 academic year. Data collection methods encompassed direct observation, field notes, tests, and documentation. The results of this study demonstrate a significant improvement in student learning outcomes. In Cycle I, the average physics score was 57.35, which increased to 83.21 in Cycle II, reflecting a marked enhancement in student performance. Moreover, the proportion of students meeting the learning completion criteria increased dramatically from 32.35% in Cycle I to 88.24% in Cycle II. These findings suggest that the peer tutoring method is an effective strategy for improving academic achievement in physics. The study concludes that peer tutoring not only fosters greater academic engagement but also contributes to more substantial learning outcomes, thus supporting its potential integration into broader educational practices for enhancing student performance in science subjects.